The Solidarity of Jesus Christ and The Comprehensive Handling of The Problem of Radicalism and Terrorism in Indonesia - Hannas Hannas; Rinawaty Rinawaty (Jurnal Didaskalia, 2018)
Jesus Christ has never shown an act of solidarity toward men as a result of being cornered by their failures to obey His commands, but as an active conduct that reflected Himself as an all-loving, all-knowing, and most sovereign Individual. This study found that: first, radicalism and terrorism in Indonesia emerged right after the fall of the New Order regime. Initially these movement only demanded justice for the oppressed Muslims. However, in their development during the nation’s post-reformation era, they position themselves as an opposition to the ruling government and threaten the existence and the continuity of the Unitary State of The Republic of Indonesia or known as NKRI (Negara Kesatuan Republik Indonesia), urging the government to revise Pancasila, the philosophical foundation of Indonesia and the Basic Constitution, UUD (Undang-Undang Dasar) 1945 to suit their own agenda. The Indonesian Goverment has been giving its serious and continous efforts to tackle this matter through the National Counterterrorism Agency or BNPT (Badan Nasional Penanggulangan Terorisme). Second, the government, religious leaders and the community must synergise to build good communication among them and to provide a fast and “down to earth” solution as to take down factors that blossom the radicalism and terrorism. Third, the Church needs to engange courageously in positioning itself to support the government that is anti-radicalism and anti-terrorism. A forum for inter-religious communication needs to be improved by advancing contributions with positive impacts rather than just becoming a passive follower; a decent interfaith dialogue and a “SERMIAH” preaching model can be adopted as options for evangelism and for achieving the spiritual maturity of the believers. The types of approaches used in this research are: historical approach, hermeneutical approach, and leadership approach.